Cloning and tissue expression of ATP-binding cassette transporters in cynomolgus macaques. (February 2022) - Uno, Yasuhiro; Yamazaki, Hiroshi
Abstract: Cynomolgus macaques are used in preclinical studies in part because of their evolutionary closeness to humans. However, drug transporters, including ATP-binding cassette (ABC) transporters, which are essential for the absorption and excretion of drugs, have not been fully investigated at the molecular level in cynomolgus macaques. In this study, ABCB4, ABCC3, ABCC4, and ABCG2 cDNAs were newly identified and characterized, along with ABCB1, ABCB11, and ABCC2 cDNAs previously identified, in cynomolgus macaques. All seven cynomolgus ABC transporters had high sequence identities (96–98%) with their human orthologs in terms of amino acid sequences and were also most closely clustered with their human orthologs by phylogenetic analysis. Furthermore, the gene structures and genomic organization were similar in cynomolgus macaques and humans. The mRNAs of these cynomolgus ABC transporters, as analyzed using the quantitative polymerase chain reaction, showed distinct tissue expression patterns. Among the ten tissues, ABCB1, ABCC2, ABCC3, and ABCG2 mRNAs were most abundantly expressed in jejunum; ABCB4 and ABCB11 in liver; and ABCC4 in kidney, which are similar to the expression patterns of human ABC transporters. These results suggest molecular similarities of the ABC transporters in cynomolgus macaques and humans. Graphical abstract: Image 1